Flat bands with band crossings enforced by symmetry representation - Hwang, Yoonseok; Rhim, Jun Won; Yang, Bohm Jung (Physical Review B, 2021)
Flat bands have band crossing points with other dispersive bands in many systems including the canonical flat-band models in the Lieb and kagome lattices. Here we show that some of such band degeneracy points of nondegenerate flat bands are unavoidable because of the symmetry representation (SR) of flat bands under unitary symmetry. We refer to such a band degeneracy point of flat bands as a SR-enforced band crossing. SR-enforced band crossing is distinct from the conventional band degeneracy protected by symmetry eigenvalues or topological charges in that its protection requires both specific symmetry representation and band flatness of the flat band, simultaneously. Even n-fold rotation Cn (n=2,3,4,6) symmetry, which cannot protect band degeneracy without additional symmetries due to its abelian nature, can protect SR-enforced band crossings in flat-band systems. In two-dimensional flat-band systems with Cn symmetry, when the degeneracy of a SR-enforced band crossing is lifted by a Cn symmetry-preserving perturbation, we obtain a nearly flat Chern band. Our theory not only explains the origin of the band crossing points of FBs existing in various models, but also gives a strict no-go theorem for isolated FBs in a given lattice arising from the SR.
Keywords: Crossing point; Degeneracy point; Dispersive band; Kagome lattice; No-go theorem; Symmetry preserving perturbations; Topological charges; Unitary symmetry